Patients' Perceptions of Nusinersen Effects According to Their Responder Status - Lilien, Charlotte; Vrscaj, Eva; Thapaliya, Gita; Deconinck, Nicolas; De Waele, Liesbeth; Duong, Tina; Haberlová, Jana; Kumhera, Markéta; Peirens, Geertrui; Szabo, Lena; Tahon, Valentine; Tang, Whitney J; et al. (Journal of clinical medicine, 2024)
Background and Objective: Patients with spinal muscular atrophy (SMA) treated with a disease-modifying therapy (DMT) are often classified as responders or non-responders based on the attainment of a specific improvement threshold on validated functional scales. This categorization may significantly impact treatment reimbursement in some countries. The aim of this research is to evaluate the perception of treatments and their benefit by patients considered as responders or non-responders. Methods: In this non-commercial multicenter study, 99 post-symptomatically treated SMA type I-III patients with a median age of 11.2 (0.39-57.4) years at treatment initiation were stratified into three groups based on their treatment outcomes, i.e., those exhibiting clinically significant improvement (N = 41), those with non-clinically significant improvement (N = 18), or those showing no improvement (N = 40). Fifteen months after treatment, the initiation patients or patients' caregivers were assessed using a patient-rated scoring system based on the Patient Global Impression of Change (PGIC) scale, comprising 22 questions targeting important aspects and tasks in the daily life of patients with SMA. Results: We found no statistical difference in the patient perception of treatment benefits in 17 out of 22 domains across patient groups. Conclusions: Our results suggest that functional motor scales do not recapitulate patients' and patients' caregivers' experience of the effect of nusinersen treatment in SMA.
Keywords: patient perception; responder; treatment response; spinal muscular atrophy; nusinersen